Dynamic Manipulation of Optical Anisotropy of Suspended Poly‐3‐hexylthiophene Nanofibers. Issue 10 (26th July 2016) - Lobov, Gleb S.; Zhao, Yichen; Marinins, Aleksandrs; Yan, Min; Li, Jiantong; Sugunan, Abhilash; Thylén, Lars; Wosinski, Lech; Östling, Mikael; Toprak, Muhammet S.; Popov, Sergei
Abstract : Poly‐3‐hexylthiophene (P3HT) nanofibers are 1D crystalline semiconducting nanostructures, which are known for their application in photovoltaics. Due to the internal arrangement, P3HT nanofibers possess optical anisotropy, which can be enhanced on a macroscale if nanofibers are aligned. Alternating electric field, applied to a solution with dispersed nanofibers, causes their alignment and serves as a method to produce solid layers with ordered nanofibers. The transmission ellipsometry measurements demonstrate the dichroic absorption and birefringence of ordered nanofibers in a wide spectral range of 400–1700 nm. Moreover, the length of nanofibers has a crucial impact on their degree of alignment. Using electric birefringence technique, it is shown that external electric field applied to the solution with P3HT nanofibers can cause direct birefringence modulation. Dynamic alignment of dispersed nanofibers changes the refractive index of the solution and, therefore, the polarization of transmitted light. A reversible reorientation of nanofibers is organized by using a quadrupole configuration of poling electrodes. With further development, the described method can be used in the area of active optical fiber components, lab‐on‐chip or sensors. It also reveals the potential of 1D conducting polymeric structures as objects whose highly anisotropic properties can be implemented in electro‐optical applications.​ Abstract : Poly‐3‐hexylthiophene nanofibers perform strong optical anisotropy, which in combination with their ability to be aligned by external electric field, provides a basis for dynamic manipulation of birefringence. Dynamic reversible modulation of birefringence or absorption through switchable reorientation of nanofibers can be implemented in a novel photonic device as an alternative to liquid crystal‐based techniques.